Secolarizzare la secolarizzazione. Una critica alla teologia sociale di Durkheim - Santambrogio, Ambrogio (SocietàMutamentoPolitica, 2017)
The essay resumes the theory asserting that Durkheim’s sociology of religion is a proper ‘social theology’ itself. It shows the similarities and differences between Durkheim’s social theology and Carl Schmitt’s ‘political theology’ interpreting both as the effect of an uncompleted secularization. Furthermore, it claims that today secularization processes need further development in order to realize a basis of social bond independent of the notion of sacred. In conclusion, it shows how some contributions in the work of Parsons, Berger and finally Habermas are useful in this perspective.